Acquired small cell lung cancer resistance to Chk1 inhibitors involves Wee1 up‐regulation. Issue 4 (26th January 2021) - Zhao, Xiaoliang; Kim, In‐Kyu; Kallakury, Bhaskar; Chahine, Joeffrey J.; Iwama, Eiji; Pierobon, Mariaelena; Petricoin, Emanuel; McCutcheon, Justine N.; Zhang, Yu‐Wen; Umemura, Shigeki; Chen, Vincent; Wang, Changli; et al.
Abstract : Platinum‐based chemotherapy has been the cornerstone treatment for small cell lung cancer (SCLC) for decades, but no major progress has been made in the past 20 years with regard to overcoming chemoresistance. As the cell cycle checkpoint kinase 1 (Chk1) plays a key role in DNA damage response to chemotherapeutic drugs, we explored the mechanisms of acquired drug resistance to the Chk1 inhibitor prexasertib in SCLC. We established prexasertib resistance in two SCLC cell lines and found that DNA copy number, messengerRNA (mRNA) and protein levels of the cell cycle regulator Wee1 significantly correlate with the level of acquired resistance. Wee1 small interfering RNA (siRNA) or Wee1 inhibitor reversed prexasertib resistance, whereas Wee1 transfection induced prexasertib resistance in parental cells. Reverse phase protein microarray identified up‐regulated proteins in the resistant cell lines that are involved in apoptosis, cell proliferation and cell cycle. Down‐regulation of CDK1 and CDC25C kinases promoted acquired resistance in parental cells, whereas down‐regulation of p38MAPK reversed the resistance. High Wee1 expression was significantly correlated with better prognosis of resected SCLC patients. Our results indicate that Wee1 overexpression plays an important role in acquired resistance to Chk1 inhibition. We also show that bypass activation of the p38MAPK signaling pathway may contribute to acquired resistance to Chk1 inhibition. The combination of Chk1 and Wee1 inhibitors may provide a new therapeutic strategy for the treatment of SCLC. Abstract : Wee1 up‐regulation is a major and novel mechanism of acquired resistance to Chk1 inhibitors in SCLC. Wee1 expression levels are correlated with resistance levels. Combination of Chk1 and Wee1 inhibitors may overcome this resistance. Combination studies of Chk1 inhibitors such as prexasertib and other agents may lead to synergistic interactions. Combinations with immune check‐point inhibitors might also be of particular interest.